(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: The promotion of different health services, including vaccination, family planning, endemic and epidemic disease control, first aid programs, and the launch of a public health policy focused on having global contours would be the tools to provide healthcare to all. Objective: Addressing women’s access to non-state healthcare in Angola, Mozambique and Guinea-Bissau, since it is the most sensitive population to international macroeconomic decisions that often limit state-funded social support and the development of the private sector. Methods: Non-state healthcare providers were referenced; they encompassed traditional therapists, third sector organizations, community and grassroots organizations. It is essential understanding the complexity of this sector in order to implement strategies to coordinate public health policies and the non-state sector supply in its multiple aspects. Results: Community Social Organizations developed a series of initiatives, many of them used the community mobilization strategy, to ensure access to basic healthcare services, mainly at mother and child scope, in Guinea Bissau. Practices used in Angola included herbal medicine and patient counseling. Patients may be informed to look for other alternatives, notably conventional medicine. Interviews with mothers in Mozambique made it possible to gather information about how they manage their children’s illnesses, as well as their inherent motivations and meanings. Conclusion: These case study mainly points toward women’s ability to intervene in vulnerable situations and depressed contexts, and the need of setting a broader dialogue among all involved parts: clients, healthcare workers, members of civil society and traditional therapists